The strategy of marketing communications as a key element of the university marketing strategy - Abuova, A.Zh. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the necessity of forming the strategy of the university marketing communications as a key component of the university marketing strategy. This importance of the marketing communications strategy is due to the aggravation of university competition for potential customers. For the successful conduct of competition, the management of any institution should be able to effectively promote the higher educational services on the market. While not only using all marketing communications tools, but also using them precisely, on the basis of a strategic approach. In this regard, the article discusses the formation of the university marketing strategy, shows a close relationship overall of the development strategy, marketing strategy and marketing communications strategy. Also, the place and role of the marketing communications strategy are defined in the hierarchy of the various university strategies. Formally, emerging from the overall university marketing, the strategy of marketing communications plays a key role in achieving of the university strategic goals. Only having a well-developed marketing communications strategy provides opportunities for the integrated, accented and effective use of marketing communications tools.